2004
DOI: 10.1177/0306624x04265283
|View full text |Cite
|
Sign up to set email alerts
|

Believing is Seeing III: Perceptions of Content in Criminal Psychological Profiles

Abstract: This study explored Kocsis and Heller's findings concerning the relationship between one's belief and the perceived accuracy of a profile. The influence of types of information was also considered. A sample of 353 participants was used in the present experiment that gauged the perception of information contained in a profile. The results supported Kocsis and Heller's earlier findings with a positive relationship found between belief and perceived accuracy. The more an individual believes in profiling, the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Two additional studies found a positive linear relationship between an individual’s initial belief in profiling and the subsequent perceived accuracy of a profile (Kocsis & Hayes, 2004; Kocsis & Heller, 2004). A follow-up study showed that an individual’s feelings about the accuracy of OP may also be a function of the professional standing of the profiler and an individual’s own beliefs about profiling (Kocsis & Middledorp, 2004). In other words, the more someone believes in the validity of profiling or is impressed by the credentials of the profiler, the more correct and useful the profiles may appear to be (Kocsis & Middledorp, 2004).…”
Section: Prior Evaluations Of Opmentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional studies found a positive linear relationship between an individual’s initial belief in profiling and the subsequent perceived accuracy of a profile (Kocsis & Hayes, 2004; Kocsis & Heller, 2004). A follow-up study showed that an individual’s feelings about the accuracy of OP may also be a function of the professional standing of the profiler and an individual’s own beliefs about profiling (Kocsis & Middledorp, 2004). In other words, the more someone believes in the validity of profiling or is impressed by the credentials of the profiler, the more correct and useful the profiles may appear to be (Kocsis & Middledorp, 2004).…”
Section: Prior Evaluations Of Opmentioning
confidence: 99%
“…A follow-up study showed that an individual’s feelings about the accuracy of OP may also be a function of the professional standing of the profiler and an individual’s own beliefs about profiling (Kocsis & Middledorp, 2004). In other words, the more someone believes in the validity of profiling or is impressed by the credentials of the profiler, the more correct and useful the profiles may appear to be (Kocsis & Middledorp, 2004). This concern was voiced by Campbell (1976), who stated that police may be more seduced by the credentials of the profiler than the profiles themselves (Petherick, 2006).…”
Section: Prior Evaluations Of Opmentioning
confidence: 99%
“…For instance, a US study on traffic police stop and search behaviors found that race was a significant predictor of being stopped by police, as certain races were perceived by the police of fitting the profile of an offender (Williams & Stahl, ). Previous research has considered the accuracy of profile predictions (e.g., Kocsis, ), the perceived accuracy of profile predictions (e.g., Alison, Smith and Morgan, ; Kocsis & Heller, ; Kocsis & Middledorp, ), and the perceived usefulness of profiles within genuine investigative scenarios (e.g., Copson, ; Jackson, Van Koppen, & Herbrink, ). However, despite the use of profiles being particularly controversial and provocative (Alison & Rainbow, ), research has failed to examine the effect such expert advice has explicitly on investigators' judgments.…”
Section: Introductionmentioning
confidence: 99%
“…Kocsis and his colleagues have published a plethora of research studies attempting to ascertain correlates of the profiling process and also uncover the most appropriate attributes of the "offender profiler" (Kocsis, 2004;Kocsis & Hayes, 2004;Kocsis & Heller, 2004;Kocsis & Middlethorp, 2004;Kocsis, Middlethorp, & Try, 2005). Kocsis (2003a) concluded that "logical and objective reasoning" were the two most important attributes individuals engaged in the profiling process should possess and that investigative experience was seemingly unrelated to performance during the evaluation exercises he conducted.…”
mentioning
confidence: 99%
“…To test this hypothesis in more detail, a later study by Kocsis and Middlethorp (2004) recruited a sample of 353 Australian university students. The study aimed to not only examine the impact of prior beliefs in profiling, but also the types of information which might be influenced under this process.…”
mentioning
confidence: 99%